Biodiesel production from sludge palm oil by esterification and transesterification processes - Alrazzouk, Adeeb Hayyan (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Sludge palm oil (SPO) is a by-product of the milling process and according to Malaysian Palm Oil Board, the annual production of SPO reaches 41 million tonnes. A huge amount of SPO needs to be utilized to produce beneficial products such as biodiesel fuel. This study develops a process to pretreat the SPO and produce biodiesel within the standard specifications for biodiesel fuel. An acid-catalyzed esterification process was carried out in pretreatment of SPO with alcohol to esterify the free fatty acid (FFA) before trasestifying the triacylglycerols (TG) with an alkaline catalyst to produce biodiesel fuel. The design of experiments for biodiesel production from SPO by esterification and transesterification processes were applied by single factor optimization. The results of SPO pretreatment indicated significant effect in the reduction of FFA content using strong acids such as hydrochloric, sulfuric and toluene-4-sulfonic monohydrate acid (PTSA) compared to weak acids such as orthophosphoric acid, acetic acid and formic acid. Based on the process performance, PTSA and sulfuric acid were selected for further optimization of esterification process. The optimum conditions for pretreatment process by esterification using PTSA as acid catalyst were 0.75% (wt/wt) dosage of PTSA to SPO, 10:1 molar ratio, 60oC temperature, 60 minutes reaction time and 400 rpm stirrer speed. Using these optimum conditions the FFA content was reduced from 22.33% to 1.4%, yield of treated SPO and conversion of FFA to fatty acids methyl ester (FAME) were 96% and 90.93% respectively. The highest yield of biodiesel after transesterification using fixed conditions was 76.62% with 0.07% FFA and 96% mol/mol ester content. The optimum conditions for pretreatment process by esterification using sulfuric acid were 1% (wt/wt) dosage of sulfuric acid to SPO, 8:1 molar ratio, 60oC temperature, 60 minutes reaction time and 400 rpm stirrer speed. Using these optimum conditions the FFA was reduced from 22.33% to 0.88%, yield of treated SPO and conversion of FFA to FAME were 96% and 96.06% respectively. The highest yield of biodiesel after transesterification using fixed conditions was 77.66% with 0.0698% FFA and 97% mol/mol ester content. The kinetics study revealed that the esterification reaction of SPO was second order reaction; moreover it was shown that the reaction rate (K) and regression coefficient (R2) were higher using sulfuric acid compared to PTSA. Sulfuric acid was selected as acid catalyst for pretreatment process of SPO based on cost, process performance and reaction rate. Optimum results of transesterification reaction were 1% wt/wt KOH with the molar ratio of methanol to oil 6:1, reaction time 30 minutes, temperature 55oC and stirrer speed 300 rpm. The highest yield of biodiesel obtained after transesterification reaction and purification was 88% with ester content of 99% mol/mol and 0.07% FFA. The biodiesel produced from SPO was favorable as compared to EN 14214 and ASTM D6751 standards.